ROLE OF CYSTATIN C IN THE DIAGNOSIS AND PROGNOSIS OF THE DEVELOPMENT OF CARDIORENAL SYNDROME IN COMORBID PATIENTS WITH ARTERIAL HYPERTENSION - Dunaieva, I.P. (World of Medicine and Biology, 2023)
The purpose of our study was to determine of diagnostic and prognostic role of cystatin C in the development of cardiorenal syndrome in the case of arterial hypertension syndrome and maximum comorbid conditions. 111 patients and 20 persons of the control group were examined. In the current examination process, they were divided into 4 groups depending on the presence of comorbid pathology in them: patients with arterial hypertension – 1 group – 22 people; patients with arterial hypertension in combination with obesity – group 2 – 30 people; arterial hypertension in combination with type 2 diabetes – group 3 – 31 people; patients with hypertension, type 2 diabetes and obesity – group 4 – 28 people. The level of cystatin C in the examined cases with arterial hypertension and various comorbidities was significantly higher compared to individuals of the control group. Significant effect of the cardiotrophin-1 residue on cystatin C. An increased level of cystatin C is associated with an increase in blood pressure, the level of cardiotrophin-1, catestatin, which ensures its role in the early development of nervous and cardiovascular complications in patients with arterial hypertension with various hormonal comorbidities and confirms the significance of the activity of adipose tissue in the development of kidney dysfunction.
Keywords: arterial hypertension; type 2 diabetes mellitus; obesity; cystatin C; cardiorenal syndrome